Endothelium-derived relaxing factor produced and released from artery and vein is nitric oxide. - Ignarro, L J (1987)
The objective of this study was to determine whether nitric oxide (NO) is responsible for the vascular smooth muscle relaxation elicited by endothelium-derived relaxing factor (EDRF). EDRF is an unstable humoral substance released from artery and vein that mediates the action of endothelium-dependent vasodilators. NO is an unstable endothelium-independent vasodilator that is released from vasodilator drugs such as nitroprusside and glyceryl trinitrate. We have repeatedly observed that the actions of NO on vascular smooth muscle closely resemble those of EDRF. In the present study the vascular effects of EDRF released from perfused bovine intrapulmonary artery and vein were compared with the effects of NO delivered by superfusion over endothelium-denuded arterial and venous strips arranged in a cascade. EDRF was indistinguishable from NO in that both were labile (t1/2 = 3-5 sec), inactivated by pyrogallol or superoxide anion, stabilized by superoxide dismutase, and inhibited by oxyhemoglobin or potassium. Both EDRF and NO produced comparable increases in cyclic GMP accumulation in artery and vein, and this cyclic GMP accumulation was inhibited by pyrogallol, oxyhemoglobin, potassium, and methylene blue. EDRF was identified chemically as NO, or a labile nitroso species, by two procedures. First, like NO, EDRF released from freshly isolated aortic endothelial cells reacted with hemoglobin to yield nitrosylhemoglobin. Second, EDRF and NO each similarly promoted the diazotization of sulfanilic acid and yielded the same reaction product after coupling with N-(1-naphthyl)-ethylenediamine. Thus, EDRF released from artery and vein possesses identical biological and chemical properties as NO.